Geographic Disparities in Stroke Outcomes and Service Access: A Prospective Observational Study - Thompson SG; Barber PA; Gommans JH; Cadilhac DA; Davis A; Fink JN; Harwood M; Levack W; McNaughton HK; Feigin VL; Abernethy V; Girvan J; et al. (Wolters Kluwer Health, Inc on behalf of the American Academy of Neurology)
BACKGROUND AND OBJECTIVE: International evidence shows that patients treated at non-urban hospitals experience poorer access to key stroke interventions. Evidence whether this results in poorer outcomes is conflicting and generally based on administrative or voluntary registry data. The aim of this study was to use prospective high-quality comprehensive nationwide patient level data to investigate the association between hospital geography and stroke patient outcomes and access to best practice stroke care in New Zealand. METHODS: This is a prospective, multi-centre, nationally representative observational study involving all 28 New Zealand acute stroke hospitals (18 non-urban), and affiliated rehabilitation and community services. Consecutive adults admitted to the hospital with acute stroke between 1 May and 31 October 2018 were captured. Outcomes included functional outcome (modified Rankin Scale (mRS) shift analysis), functional independence (mRS scores 0-2), quality of life (EQ5D-3L), stroke/vascular events, and death at 3, 6, and 12 months and proportion accessing thrombolysis, thrombectomy, stroke units, key investigations, secondary prevention, and inpatient/community rehabilitation. Results were adjusted for age, sex, ethnicity, stroke severity/type, co-morbidities, baseline function, and differences in baseline characteristics. RESULTS: Overall, 2,379 patients were eligible (mean (standard deviation) age 75 (13.7); 51.2% male; 1,430 urban; 949 non-urban). Patients treated at non-urban hospitals were more likely to score in a higher mRS category (greater disability) at three (aOR=1.28, 1.07-1.53), six (aOR=1.33, 1.07-1.65) and twelve months (aOR=1.31, 1.06-1.62) and were more likely to have died (aOR=1.57, 1.17-2.12) or experienced recurrent stroke and vascular events at 12 months (aOR=1.94, 1.14-3.29 and aOR=1.65, 1.09-2.52). Fewer non-urban patients received recommended stroke interventions including endovascular thrombectomy (aOR=0.25, 95% confidence interval 0.13-0.49), acute stroke unit care (aOR=0.60, 0.49-0.73), antiplatelet prescriptions (aOR=0.72, 0.58-0.88), ≥60 minutes daily physical therapy (aOR=0.55, 0.40-0.77) and community rehabilitation (aOR=0.69, 0.56-0.84). DISCUSSION: Patients managed at non-urban hospitals experience poorer stroke outcomes and reduced access to key stroke interventions across the entire care continuum. Efforts to improve access to high quality stroke care in non-urban hospitals should be a priority.
© 2022 The Author(s)
Keywords: 1103 Clinical Sciences; 1109 Neurosciences; 1702 Cognitive Sciences